Changes of dietary fiber and starch composition of processed potato products during domestic cooking - Thed, S. T.; Phillips, R. D. (Elsevier, 1995)
The effects of domestic cooking on dietary fiber and starch composition of selected processed potato products were evaluated. Microwave-heating and deep-fat frying reduced an appreciable amount of in-vitro digestible starch and significantly increased both the resistant starch (RS) and water-insoluble dietary fiber (IDF), while boiling and baking had less effect. Water-soluble dietary fiber content was not affected by any of the domestic cooking methods studied. The significant correlation between IDF and RS supported the idea that some of the starch in cooked potato had become indigestible by amylolytic enzymes, and this RS might contribute to the observed increment in the IDF fraction.